Local Nonprofit Organizations in a Post-Katrina Landscape: Help in a Context of Recovery. (September 2015) - Jenkins, Pamela; Lambeth, Tara; Mosby, Kim; Van Brown, Bethany
In this study, we examine the role of local New Orleans nonprofit agencies in disaster and how these local nonprofits become a part of the disaster management process. The dominant disaster management framework, and to some degree the social vulnerability approach, affect the design of postdisaster relief programs, projects, and policies. The new Federal Emergency Management Agency framework asks nonprofits to contribute to postdisaster relief, as well as predisaster preparedness. This increased inclusion of local nonprofits in disaster recovery presents specific challenges. The present case study uses multiple sources of data collected over a 10-year period from nonprofit agencies. Primary data collection included interviews, focus groups, and observations of nonprofits; we also collected data from a series of community workshops for nonprofit agencies. We found the nonprofits in New Orleans that reframed their work to fit into the postdisaster context proved to be the most resilient. Their ability to adapt and be reflexive emerged as the most important skills in a postdisaster landscape. However, in the midst of their substantial post-Katrina accomplishments, the future for local nonprofits in disaster depends on their relationship with the federal government and their impact on federal policy.